Characterization of Pseudomonas aeruginosa Isolates Obtained from Patients in Canadian Hospitals: Results of the CANWARD 2007 Study - Andrew Walkty; Melanie DeCorby; Kim Nichol; Melissa McCracken; Michael R Mulvey; James A Karlowsky; Daryl J Hoban; George G Zhanel (Canadian Journal of Infectious Diseases and Medical Microbiology)
INTRODUCTION: Pseudomonas aeruginosa is an important nosocomial pathogen. The purpose of the present study was to evaluate the antimicrobial susceptibility profile of P aeruginosa isolates obtained from patients in different areas of Canadian hospitals. METHODS: From January to December 2007 inclusive, 12 sentinel hospitals across Canada submitted clinical isolates from patients attending emergency rooms, medical wards, surgical wards and intensive care units (ICUs) (the Canadian Ward Surveillance Study [CANWARD 2007]). Each centre was asked to submit clinical isolates (consecutive, one per patient per infection site) from blood (n=360), respiratory (n=200), urine (n=100) and wound/intravenous (n=50) infections. Susceptibility testing was performed using Clinical and Laboratory Standards Institute broth microdilution methods. Multidrug-resistant (MDR; resistant to at least three different antimicrobial classes) isolates were typed by pulsed-field gel electrophoresis. RESULTS: In total, 451 P aeruginosa isolates were collected (representing 7% of all CANWARD 2007 isolates). The rank order of antimicrobial susceptibility was as follows (percent susceptible): amikacin (93.1%) = piperacillin/tazobactam (93.1%) > meropenem (87.4%) > cefepime (69.4%) > ciprofloxacin (67.2%) > gentamicin (66.1%) > levofloxacin (60.5%). Reduced susceptibility to cefepime, meropenem and levofloxacin was observed more frequently among ICU isolates (P<0.05). Thirty-four isolates (7.5%) were MDR. MDR isolates were more likely to be obtained from patients in an ICU (P=0.003) and less likely to come from a bloodstream source (P=0.008). Excluding colistin (polymyxin E), amikacin and piperacillin/tazobactam, followed by meropenem, were the most active antimicrobials evaluated versus the MDR isolates. All of the MDR isolates were susceptible to colistin. The majority of MDR isolates were genetically unrelated. CONCLUSIONS: P aeruginosa is common among clinical specimens from patients in Canadian hospitals. Of the antipseudomonal antimicrobials evaluated, amikacin, meropenem and piperacillin/tazobactam demonstrated the greatest in vitro activity. Isolates with reduced antimicrobial susceptibility and MDR isolates were more often obtained from ICU patients. All of the MDR isolates remained susceptible to colistin.